2020
DOI: 10.1308/rcsann.2019.0109
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal and multicentric breast cancer, is it time to think again?

Abstract: Multifocal multicentric breast cancer has traditionally been considered a contraindication to breast conserving surgery because of concerns regarding locoregional control and risk of disease recurrence. However, the evidence supporting this practice is limited. Increasingly, many breast surgeons are advocating breast conservation in selected cases. This short narrative review summarises current evidence on the role of surgery in multifocal multicentric breast cancer and shows that when technically feasible the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
19
0
4
Order By: Relevance
“…Oncoplastic breast conservation surgery has been shown as a safe alternative to mastectomy and immediate breast reconstruction in selected patients based on the combined data of iBRA-2 and TeaM studies of 2916 patients (17). Further, the Scottish audits of oncoplastic breast conservations indicate that oncoplastic surgery can widen the indications for breast conservation, and provide good oncological outcome with low complication rates in our hands, hence it can be a reasonable alternative to mastectomy with immediate reconstruction (18)(19)(20)(21). One unit in Italy did offer immediate breast reconstruction even during the peak of the COVID-19 pandemic as it is indicated by Fragetti et al who reported 15 nipple-sparing mastectomies with immediate J o u r n a l P r e -p r o o f reconstruction done in 13 patients, although reconstructive techniques were not disclosed (14).…”
Section: Discussionmentioning
confidence: 99%
“…Oncoplastic breast conservation surgery has been shown as a safe alternative to mastectomy and immediate breast reconstruction in selected patients based on the combined data of iBRA-2 and TeaM studies of 2916 patients (17). Further, the Scottish audits of oncoplastic breast conservations indicate that oncoplastic surgery can widen the indications for breast conservation, and provide good oncological outcome with low complication rates in our hands, hence it can be a reasonable alternative to mastectomy with immediate reconstruction (18)(19)(20)(21). One unit in Italy did offer immediate breast reconstruction even during the peak of the COVID-19 pandemic as it is indicated by Fragetti et al who reported 15 nipple-sparing mastectomies with immediate J o u r n a l P r e -p r o o f reconstruction done in 13 patients, although reconstructive techniques were not disclosed (14).…”
Section: Discussionmentioning
confidence: 99%
“…33 In a study by Massanat et al, they reported that BCT is not contraindicated in selected cases in MF/MC BCs. 34 In a similar study, Koppiker et al, proposed extreme oncoplasty (EO) instead of BCT in MF/MC cases. 35 Nijenhuis et al, reported that BCT may performed in most MF/MC cases.…”
Section: Resultsmentioning
confidence: 99%
“…37 Many authors have reported that BCT can be performed in some selected MF/MC cases. 20,34,37,38 However, in a study conducted by Edwards et al, 414 of 567 cases with BCT were reviewed, and histological tumor positive margin was found in 23%, and residual tumor was found in 61 cases. 39 In a study by Akbulut et al, miR-429 expression was shown to increase only in MBCs, while miR-182-5p and miR-96-5p expression increased in both MBC and UBCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In fact, we offer BCS for potentially poorer prognostic single-tumour patients or in-situ disease but continue to exclude larger or MFMC tumours. 5 The introduction of screening coupled with ultrasonography (US) and magnetic resonance imaging (MRI) has allowed us to more sensitively identify multifocal and multicentric cancers, making diagnosis of these "extreme" cases more common, thus surgical options more valid for debate. [6][7][8] Oncoplastic breast conservation (OBC) relies on applying plastic surgery principles within the context of sound oncological resection.…”
Section: Introductionmentioning
confidence: 99%